Photorealistic computer-generated images are difficult to distinguish from digital photographs: a case study with professional photographers and photo-editors. (November 2019) - Lehmuskallio, Asko; Hӓkkinen, Jukka; Seppӓnen, Janne
There are strict guidelines on photoediting in newsrooms and serious professional repercussions for any failure to adhere to them, while computer-generated imagery is increasingly used in other areas of visual communication. This article presents empirical research on the ability of professional photographers and editors to distinguish photographs from photorealistic computer-generated images by looking at them on a screen. The results show clearly that those studied ( N = 20) are unable to distinguish one from another, suggesting that it is increasingly difficult to make this distinction, particularly since most viewers are not as experienced in photography as those studied. Interestingly, the participants continue to share a conventional understanding of photography that is not in line with current developments in digital photography and digital image rendering. Based on their findings, the authors suggest there is a need for developing a particular visual literacy that understands the computational in digital photography and grounds the use of digital photography among particular communities of practice. When seeing photographs on screens, journals, exhibitions, or newspapers, viewers might actually be looking at computer-generated simulations, and vice versa.